SQL server 2008 administration instant reference - Lee, Michael 1966- (Wiley Pub., 2009)
"Perfect companion to any SQL Server 2008 book, providing fast, accurate answers on the spot for millions of IT professionals System and database administrators, IT consultants, and database application developers often need quick answers and practical solutions for SQL Server issues. This convenient guide offers you quick referencing for the product and database topics you need most. If you're an IT administrator looking for the essentials in the day-to-day tasks of administering SQL Server 2008, you'll appreciate this book's design for providing quick and easy look up of solutions and tables, lists, and step-by-step instructions for answers on the spot. SQL Server 2008 Instant Administration Reference is a guide that you want to keep within reach. SQL Server is Microsoft's bestselling database manager; the 2008 version offers enhanced security and high availability, encouraging users to upgrade Features thumb tabs, secondary and tertiary tables of contents, and special heading treatments to provide quick and easy lookup, as well as quick-reference tables and lists to provide answers on the spot Covers installing, configuring, managing, and maintaining SQL Server; optimizing server performance; and troubleshooting SQL Server 2008 Administration Instant Reference answers the questions you encounter most often in your daily work"--Provided by publisher
Print version record
Keywords: SQL server; Database management; Relational databases; Bases de données; Gestion; Bases de données relationnelles; COMPUTERS; Data Processing